The Injury Incidence and Treatment Experience among Elite and Beginner Thailand Bodybuilders - Potchara Chinnasee; Thanatpong Sukwong; Pranee Liamputtong; Dusanee Suwankong; Nur Ikhwan Mohamad; Ali Md Nadzalan (OVS LLC, 2023)
Background. Bodybuilding is a sport where a person should do a lot of weight training while in the same time having a strict diet control. Due to this, they are believed to have higher chances of getting injured. However, lack of research has been conducted on the incidence of injuries and the treatment history among bodybuilders in Thailand. Therefore, the purpose of this study was to investigate and compare the incidence of injuries and treatment experience between elite and beginner Thailand bodybuilders. Material and methods. 157 bodybuilders who were registered as members of the Thailand Bodybuilding and Physique Sports Association (since 2020-2021) were recruited as participants in this study. They were divided in to two groups, namely elite (more than 5 years of sports training) and beginner (less than 5 years of sports training). A valid and reliable questionnaire was used to collect the data from the participants. Results. There was no significant difference in the most common period of injury between the beginner and elite groups. The most common period of injury for both groups was found to be during diet period (beginner 55.43%; elite 55.38%) followed by bulk period, off season and competition period, respectively. For the injury area, there was no difference between the groups, with the lower back (beginner 63.04%; elite 52.31%) being the most common area of injury, followed by shoulder, chest, finger and wrist. There was also no significant difference in treatment between the groups in the first 48 hours after injury. Most of the athletes in both groups had rest (beginner 80.43%; elite 81.53%) and applied cold (beginner 61.96%; elite 73.85%) to their injury area. Additionally, the beginner group of Thai bodybuilders visited the physical therapist more often than the elite group did (p < 0.01). At the same time, there was no significant difference in medical doctor, sports scientist, coach and self-treatment and rehabilitation between both groups. However, most of athletes from both groups mainly resorted to self-treatment. Conclusions. The study findings are expected to be valuable for the bodybuilding association, coaches and athletes to take extra precautions regarding injury in the future.